2014
DOI: 10.2147/dddt.s68501
|View full text |Cite
|
Sign up to set email alerts
|

Schisandra chinensis regulates drug metabolizing enzymes and drug transporters via activation of Nrf2-mediated signaling pathway

Abstract: Drug metabolizing enzymes (DMEs) and drug transporters are regulated via epigenetic, transcriptional, posttranscriptional, and translational and posttranslational modifications. Phase I and II DMEs and drug transporters play an important role in the disposition and detoxification of a large number of endogenous and exogenous compounds. The nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a critical regulator of a variety of important cytoprotective genes that are involved in disposition and detoxification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 95 publications
0
7
0
1
Order By: Relevance
“…Schisandra chinensis and its components have antioxidant and neuroprotective effects through Nrf2 transcriptional activation (Chen et al, 2008 ; He et al, 2014 ; Giridharan et al, 2015 ). Therefore, we investigated the effect of SSCE on the Nrf2 pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schisandra chinensis and its components have antioxidant and neuroprotective effects through Nrf2 transcriptional activation (Chen et al, 2008 ; He et al, 2014 ; Giridharan et al, 2015 ). Therefore, we investigated the effect of SSCE on the Nrf2 pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The main ingredients of SSC, which include gomisin A/J/N and schisandrin (schizandrin) A/B/C, were also separated from the FSC (Lu and Chen, 2009 ; Zheng et al, 2014 ; Zhu et al, 2015 ). FSC extract and its constituents have beneficial effects in the treatment of various diseases including neurological diseases, such as cognitive and motor dysfunction (Panossian and Wikman, 2008 ), through anti-apoptotic (total extract and schisandrin B), anti-oxidative (total extract, schisandrin A, and schisandrin B), synaptic transmission (deoxyschizandrin), and anti-neuroinflammatory activities (schisandrin B and gomisin A) (Chen et al, 2008 ; Fu et al, 2008 ; He et al, 2014 ; Wang, X. et al, 2014 ; Giridharan et al, 2015 ; Zhang et al, 2015 ), which confirms the effects of FSC that have been reported by practitioners of traditional medicine (Huh, 1613 ). SSC also includes anwuweizic acid, daucosterol, (+)-deoxyschizandrin, (–)-dihydroguaiaretic acid, gomisin N, henrischinin A-C, schicagenin A-C, schinchinenin A-H, schinchinenlactone A-C, γ-schizandrin, β-sitosterol, tetradecanoic acid, and wuweizisu C (Shi et al, 2011 ; Song et al, 2013 ; Zheng et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The fruits, leaves, and stems of Schisandra chinensis contain dibenzo[a,c]cyclooctadiene lignans and are thus suggested to have bioactive properties [ 17 ]. An in vitro study examining the hepatic effects of Schisandra chinensis confirmed its role in activating Nrf-2 on HepG2 cell lines [ 18 ]. Nrf-2 activation is known to mediate the activation of target genes involved in phase I and phase II liver metabolism [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These are exclusively expressed in the basolateral membrane of the liver and are responsible for the uptake of a wide variety of endogenous and exogenous substrates, such as antidiabetics, antineoplastics, HMG-CoA reductase inhibitors and so on ( Klatt et al, 2013 ; Van De Steeg et al, 2013 ; Kunze et al, 2014 ; Marada et al, 2015 ). Furthermore, several studies have shown that many herbal ingredients may impact the transportation of substrates mediated by OATP1B1/1B3 ( Mandery et al, 2012 ; Zhang et al, 2013 ; He et al, 2015 ; Sheng et al, 2015 ). The interactions among these herbal ingredients based on OATPs might be one of the important compatibility mechanisms of TCM.…”
Section: Introductionmentioning
confidence: 99%